Nuclear incident could prompt more costly inspections [power plants]. - Sweet, W. (IEEE spectrum)
On 7 May 2002, the U.S. Nuclear Regulatory Commission (NRC, Rockville, Md.) formally heard the operator of an Ohio reactor report on the causes of a situation that could very nearly have led to a serious loss-of-coolant accident. The situation is now fairly well understood and can be considered isolated, but questions remain as to whether nuclear surveillance both by the NRC and plant operators is as rigorous as it needs to be.